TRANSFORMASI KURIKULUM PAI NASIONAL DI ERA KURIKULUM MERDEKA RELEVANSI, IMPLEMENTASI, DAN EVALUASI - Ekania Sausan Zahro; Fikri Najmuddin Abdullah; Habib Al Ridho; Alhidayah Rizki Putra; Kamarul Huda; Sangkot Abdullah Efendi Harahap (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the transformation of the national Islamic education curriculum within the framework of the Merdeka curriculum, focusing on the aspects of relevance, implementation, and evaluation. The research employs a qualitative approach using a library research method through the review of educational policy documents, Islamic education learning outcomes, and relevant and up-to-date scholarly literature. Data analysis is conducted using content analysis to obtain a comprehensive understanding of the paradigm shift in the Islamic education curriculum. The findings indicate that the Islamic education curriculum under the Merdeka curriculum has strong relevance to the needs of twenty-first-century learners, particularly in strengthening character, religious moderation, and reflective thinking skills. In terms of implementation, the Merdeka curriculum provides flexibility for teachers to design contextual and student-centered learning, although challenges remain related to teacher readiness and limited learning resources. Regarding evaluation, there is a shift toward authentic assessment that holistically measures learning processes, attitudes, and religious practices, which requires strengthening teachers’ assessment competencies to ensure objectivity and consistency. This study concludes that the transformation of the Islamic education curriculum within the Merdeka curriculum has the potential to improve the quality of Islamic education learning, provided it is supported by consistent policies,